Under the knife remarkable stories from the history of surgery - Laar, Arnold van de (John Murray, 2018)
'This is history with a surgeon's touch: deft, incisive and sometimes excruciatingly bloody' The Sunday Times'Utterly eccentric and riveting' Mail on Sunday 'Eye-opening and, frequently, eye-watering . . . a book that invites readers to peer up the bottoms of kings, into the souls of rock stars and down the ear canals of astronauts' The Daily TelegraphHow did a decision made in the operating theatre spark hundreds of conspiracy theories about JFK How did a backstage joke prove fatal to world-famous escape artist Harry Houdini How did Queen Victoria change the course of surgical historyThrough dark centuries of bloodletting and of amputations without anaesthetic to today's sterile, high-tech operating theatres, surgeon Arnold van de Laar uses his experience and expertise to tell an incisive history of the past, present and future of surgery.From the dark centuries of bloodletting and of amputations without anaesthetic to today's sterile, high-tech operating theatres, Under the Knife is both a rich cultural history, and a modern anatomy class for us all.